Dharma and halacha comparative studies in Hindu-Jewish philosophy and religion - Theodor, Ithamar, 1959-; Greenberg, Yudit Kornberg (Studies in comparative philosophy and religion, 2018)
"This work provides an anthology of close textual readings and examinations of a wide range of topics by leading scholars in interreligious scholarship and Hindu-Jewish dialogue, offering innovative approaches to categories such as ritual, sacrifice, ethics, and theology while underscoring affinities between Hindu and Jewish philosophy and religion" --